Social Networks, Social Media and Absorptive Capacity in Regional Small and Medium Enterprises (SMES) in Australia - Bosua, Rachelle; Evans, Nina; Sawyer, Janet (Australian and International Journal of Rural Education, 2013)
Small and Medium Enterprises (SMEs) are major sources of prosperity and employment and are viewed as critical to regional development in Australia. A key factor to foster productivity and growth in SMEs is their ability to identify, acquire, transform and exploit external knowledge. This ability, referred to as the ‘absorptive capacity (AC)’ of a firm, depends on formal and informal processes of socialisation by developing relevant and extensive informal networks (also referred to as social networks). This research explores how Australian SMEs in regional areas harness their Social Networks (SNs) and Social Media to acquire external knowledge towards innovation. A qualitative case study research approach is followed to collect data from 12 SMEs in regional South Australia using interviews as the key data collection instrument. Findings suggest that although SMEs draw on informal and formal SNs to acquire new knowledge, 1) this process is intuitive and SMEs should be made more aware of the value of these networks, 2) the use of Social Media to support social networking activities to acquire new knowledge is scant and 3) SMEs require more educational support to enhance their knowledge of the value of SNs and social media in acquiring new knowledge towards innovation.